The impact of rural human capital on household energy consumption structure: Evidence from Shaanxi Province in China - Xiuqing Li; Hui Mao; Lan Fang (Sustainable Futures, 2024)
The structure of rural household energy consumption is crucial for rural residents' living standards and quality of life, constituting an integral component of energy transition and promoting Chinese-style modernization. Meanwhile, rural human capital is a prerequisite for agricultural and rural modernization. Drawing on survey data from 791 households in Shaanxi Province, this study empirically examines the impact and mechanisms of human capital on the household energy consumption structure with the ordinary least square (OLS) model and instrumental variable (IV) method. The findings indicate that human capital significantly reduces traditional energy consumption while increasing the adoption of transitional and advanced energy. This conclusion remains robust after rigorous testing. Mechanism analysis reveals that human capital facilitates the shift from traditional to transitional and advanced energy by enhancing purchasing power, environmental awareness, and the frequency of energy-saving technology usage within households. Further analysis demonstrates that higher levels of human capital correlate with a greater likelihood of households transitioning from traditional energy to transitional and advanced energy. Particularly, households with a high school education exhibit a significant increase in the consumption of transitional and advanced energy while notably reducing traditional energy consumption. Moreover, compared to low-income households, human capital has a significantly positive effect on increasing the adoption of advanced energy in high-income households. Hence, prioritizing investment in rural education, providing more educational resources, improving school facilities, and implementing incentive policies to emphasize education within households are recommended strategies to enhance rural residents' human capitals. This, in turn, facilitates their adoption of transitional and advanced energy, reducing dependence on traditional energy.
Keywords: D13; D31; J24; Q43; 330; human capital; energy consumption structure; income level; environmental awareness